Kleist vs. Musschenbroek – a difficult way to truth - Jerzy Sawicki (Studia Historiae Scientiarum)
On October 11, 1745, a German scientist Ewald Georg (Jürgen) Kleist in Cammin in Pommern (today Kamień Pomorski) discovered both the phenomenon of storing electricity in a glass vessel with water, and a new device – an electric capacitor. Kleist quickly and correctly announced his discovery to the scientific community.